The compact-strip-produced martensitic steel possessing better resistance to hydrogen-induced delayed cracking. (June 2023) - Wang, Jing; Xue, Peng; Zhang, Laiqi; Qiao, Yi; Zhu, Xiaodong; Wang, Shuize; Zhong, Yong; Mao, Xinping
Abstract: Hydrogen-induced delayed cracking (HIDC) of martensitic steel limits its extensive application in lightweight automobile industry. Up to now, the research regarding HIDC of compact-strip-produced martensitic steel (CSP-MS) has not been reported. The HIDC behavior of CSP-MS steel was investigated. It was found that with the increase of hydrogen-charging current density in slow strain rate tensile tests, tensile strength of the two martensitic steels is relatively similar, however elongation decreases significantly while hydrogen embrittlement index ( I HE ) increases dramatically. The I HE of CSP-MS steel is lower than that of conventional produced martensitic steel (Con-MS) under all test conditions, as indicating that CSP-MS steel has better resistance to HIDC. The small size of TiN in CSP-MS steel leads to delayed initiation of microcrack than that of Con-MS steel, which is the mechanism for its superior resistance to HIDC. This work provides a new avenue for large-scale application of martensitic steel in automotive industry. Graphical abstract: Image, graphical abstract